2012
DOI: 10.1108/14668201211217512
|View full text |Cite
|
Sign up to set email alerts
|

The governance of adult safeguarding: findings from research

Abstract: Purpose -This article reports the findings from research into the governance of adult safeguarding policy and practice in England, with particular focus on interagency partnership arrangements expressed through Safeguarding Adults Boards.Design -The study comprised a systematic search and thematic analysis of Englishlanguage literature on adult safeguarding governance, a survey of Safeguarding Adults Board documentation, and key informant interviews and workshops with professionals involved in adult protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…Further material was sought through a systematic search of the literature, although little of direct relevance -that is, regarding Scottish adult safeguarding policy and practice since 2007 -was found. Consequently, references are made where relevant to literature addressing the rest of the UK -in particular Braye et al's (2012) paper reporting research on adult safeguarding governance in England -and Scotland experience before the implementation of the Act. For clarity this paper refers to English Safeguarding Adults Boards (SABs) to differentiate them from the Scottish APCs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further material was sought through a systematic search of the literature, although little of direct relevance -that is, regarding Scottish adult safeguarding policy and practice since 2007 -was found. Consequently, references are made where relevant to literature addressing the rest of the UK -in particular Braye et al's (2012) paper reporting research on adult safeguarding governance in England -and Scotland experience before the implementation of the Act. For clarity this paper refers to English Safeguarding Adults Boards (SABs) to differentiate them from the Scottish APCs.…”
Section: Methodsmentioning
confidence: 99%
“…Mackay (2008) has suggested that comparative studies within the UK could improve understanding of this area of law and practice. While recognising that social services in Scotland have a somewhat different history and character from provision in the rest of the UK (Brodie et al, 2008;Watson and West, 2008), with any parallels therefore being drawn with care, this article will offer findings about governance of adult safeguarding in Scotland and compare these with outcomes derived from a study in England (Braye et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The first investigated partnerships and regulation in adult protection (Penhale et al, 2007) and identified wide variation in the status and operations of Boards (also referred to as Committees). This study found that Boards were largely dependent on middle managers in local agencies to get adult protection systems working effectively (Manthorpe, Hussein, et al, 2010) More recently, a Department of Health commissioned study was conducted by Braye, Orr and Preston Shoot (2011) on adult safeguarding governance. This provided valuable insights into the work of Boards and their potential effectiveness.…”
Section: Two Studies In England and Wales Have Considered The Workingmentioning
confidence: 96%
“…This provided valuable insights into the work of Boards and their potential effectiveness. Braye et al (2011) compiled a list of characteristics that had featured in audit, inspectorate and other similar reports which gave rise to commendations or a 'positive review on the safeguarding element of inspections ' (p14). What might be termed quality indicators included an 'informative annual report' although this was last in the long list of the characteristics identified by Braye et al (2011).…”
Section: Two Studies In England and Wales Have Considered The Workingmentioning
confidence: 99%
See 1 more Smart Citation